Health manpower development in Nepal: A historical perspective - Shah, M (Kathmandu University Medical Journal, 2010)
DOI: 10.3126/kumj.v7i3.2746 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 325-327